Reviewing the Literature of Inventory Models under Trade Credit Contact - Zohreh Molamohamadi; Napsiah Ismail; Zulkiflle Leman; Norzima Zulkifli (Discrete Dynamics in Nature and Society)
In the classical inventory models, it was assumed that the buyer pays for the purchased items as they are received from the seller. In practice, however, the seller allows the buyer to settle the account with a delay period. Such a contract has attracted the attention of many researchers and practitioners in recent years. Thus, this paper addresses the researches with delay in payment and presents pertinent information about developments and extensions of such models to provide an up-to-date review of the studies conducted since 1973 and assist in developing the future researches.